Language education policy in Portuguese public universities: the voices of institutional stakeholders - Pinto, Susana (2018)
Acknowledging the importance of the ideological language component in language policy and planning within a micro-level language-planning framework, this paper sets out to identify and discuss the social representations of Portuguese higher education institution (HEI) stakeholders concerning: (i) language teaching and learning in HEIs and (ii) the development of language education policies in this particular context. Based on a questionnaire and semi-structured interviews with the stakeholders responsible for the pedagogical strategy, specifically five Vice-Rectors for Education at their respective Portuguese public universities, their common perspective points to tension between, on one hand, the value they attribute to a diversified language teaching and learning in terms of the quantity of languages offered and to the strategic development of multilingual language education policies and, on the other hand, the prominence of institutional initiatives and actions relying primarily on English.